Políticas de formação de professores: o alcance do PARFOR na região de abrangência da Unioeste de 2010 a 2014 - Rojo, Francisca de Carvalho (2016)
The National Plan of Teachers Formation for Basic Education-PARFOR is a government plan of emergency action for attending the teachers in an effective exercise in the public networks of teaching of basic education. The research had as a general objective to describe the quantitative impact of the Plan on the Coverage Area of UNIOESTE in between the years 2010 and 2014, with the intention of determining if the PARFOR achieved its quantitative objectives in its modalities for the situation. The Plan was instituted by a Regulatory Ordinance moa no de 2009 to attend to the Law of Directives and Bases of Education-LDB n° 9.394 of December 20th of 1996. The type of research was regularized by its exploratory characteristic, based in primary and secondary sources. The primary ones circumscribe themselves to the official documents from various involved institutions and normative contours of different hierarchies and the secondary ones in few bibliographies, having in mind the recent insertion of the Plan. The data was obtained from the university’s website, in the academic departments of campuses, as well as general coordination of the PARFOR. With the research, it was possible to evaluate the guiding documents of the Plan, as well as comprehending historically the development process of the formation of teachers in Brazil, a subject already exhaustively studied. It was found that the PARFOR could be considered a relevant action to the teacher’s formation in effective exercise in public network even with the many existing barriers in the development of the Plan. The results pointed to a necessity to prioritize educational policies of teacher training that are better planned and, so that the desired objectives can possibly be achieved.